Self-construal priming selectively modulates the scope of visual attention - Liu, Zhuozhuo; Cheng, Menxue; Peng, Kaiping; Zhang, Dan (Frontiers in Psychology, 2015)
Self-concept is one of the major factors to explain the cultural differences between East Asians and Westerners. In the field of visual attention, most studies have focused on the modulation of visual spatial-based attention, whereas possible influences of culture or self-concept on other types of visual attention remain largely unexplored. The present study investigated the possible modulation of visual feature-based attention by self-concept, using a within-group self-construal priming design. The experiment paradigm employed visual stimuli consisted of two intermixing random dot clouds presented in the focal visual field with red and green colors. After primed with an interdependent, independent or neutral self-construal, the participants were instructed to attend to one of the focally presented dot cloud and respond to occasional luminance decrement events of the attended dot cloud. The detection of the focal events was found to be significantly faster when exogenously cued by a peripheral dot cloud of either the same or different colors as the attended focal dot cloud (congruent / incongruent), compared to the uncued condition. More importantly, the self-construal priming took effect only on the reaction time (RT) differences between the congruent and incongruent cued conditions: the participants responded much slower to incongruent cued events than congruent cued events under interdependent self-construal priming, while the RT difference was significantly smaller under independent self-construal priming. A closer look on the results suggests that the attention scope is selectively modulated by self-construal priming, and the modulation is mainly reflected by varying the degree of suppression on the processing of the incongruent contextual stimuli that do not share visual features with the focal object. Our findings provide new evidences that could possibly extend the current understanding on the cultural influence on visual attention.